Linking topology of large DNA molecules - Marko, John F. (2010)
Double helix DNA molecules, the carriers of genetic instructions in cells, are strongly affected by their topological properties. Two distinct and biologically important types of linking are associated with double helix DNAs: ‘internal’ linking of the two strands of individual double helices, and ‘external’ linking of separate double helix DNAs. Constraint of internal linking gives rise to internal torsional stress and supercoiling of circular DNAs. External linking is a likely outcome of DNA replication, and must be eliminated by the cell in order to separate duplicated DNAs. I outline some of the physics and biology connected with both internal and external linking.